Development of AI-Powered Optimization Frameworks for Enhancing Chemical Processes in Sustainable and Energy-Efficient Water Treatment - Ayodeji Idowu Taiwo; Lawani Raymond Isi; Michael Okereke; Oludayo Sofoluwe; Gilbert Isaac Tokunbo Olugbemi; Nkese Amos Essien (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Integrating artificial intelligence (AI) into water treatment processes offers transformative potential for enhancing chemical operations' sustainability and energy efficiency. This paper explores the development of AI-powered optimization frameworks to address the dual challenges of resource conservation and environmental protection in water treatment. It begins by outlining the theoretical foundations of AI in chemical process optimization, emphasizing the principles of sustainable engineering and the intersection of AI with water treatment technologies. The paper also discusses the challenges in deploying AI, such as data quality and energy constraints, while highlighting opportunities for improving chemical efficiency, reducing waste, and scaling solutions across diverse applications. A proposed optimization framework conceptual model is presented, featuring key components such as real-time data acquisition, machine learning analytics, and adaptive process control, along with synergies with complementary technologies like IoT and digital twins. Finally, the paper provides recommendations for advancing research, fostering interdisciplinary collaboration, and promoting practical implementation. This framework improves operational efficiency and sustainability and exemplifies AI's pivotal role in addressing critical global water challenges.
Keywords: Artificial Intelligence; Water Treatment; Chemical Process Optimization; Sustainability; Energy Efficiency; Internet of Things (IoT)